Multidisciplinary Presurgical Education: Clinical Impact on Children With Orofacial Clefts Undergoing Maxillary Distraction via Rigid External Distraction. (January 2023) - Kim, Erinn N.; Moss, Whitney D.; Rosales, Megan N.; Lyon, Natalee; Lotz, Analise; Yamashiro, Duane K.; Gociman, Barbu R.; Siddiqi, Faizi A.; Johns, Dana N.
Objective: Treatment of severe maxillary hypoplasia is commonly addressed via distraction osteogenesis with a rigid external device (RED). While effective, this method can be socially stigmatizing in an already vulnerable patient population. To prepare children and their caregivers for life with a RED and decrease peri-operative anxiety, we instituted a multidisciplinary pre-surgical education session (MPES). This educational team involves our cleft care coordinator, child life specialist, orthodontist and plastic surgeon 2 weeks prior to surgery. We reviewed the impact of this intervention by examining clinical outcomes before and after its implementation. Design: From February 2017 to February 2020, a retrospective chart review was performed to include patients with orofacial clefts and maxillary hypoplasia who underwent maxillary distraction osteogenesis with RED at our center before (28 patients) and after (29 patients) the implementation of MPES. Results: MPES was associated with a significantly shorter length of stay compared to controls who did not receive MPES (3.6 vs 3.1 days, p < 0.03) and significantly decreased usage of inpatient narcotic pain medication compared to controls (16.8 morphine equivalents vs 31.8 morphine equivalents, p < 0.02). Our intervention also demonstrated a trend towards decrease in minor complications but did not achieve statistical significance p = 0.32). Conclusions: Multidisciplinary presurgical education is a beneficial adjunct in the care of patients with orofacial clefts and maxillary hypoplasia undergoing maxillary advancement with a RED.